Structural architecturing and hydrocarbon reservoir potential of Sakesar Limestone: Surghar Range, North Pakistan : Structural architecturing and hydrocarbon reservoir potential of Sakesar Limestone: Surghar Range, North Pakistan - Iftikhar Alam; Syed Abbas Sultan; M. Waseem Khan (International Journal of Economic and Environmental Geology, 2017)
The Surghar Range western extension of the Trans-Indus ranges constitutes the southeastern anterior fold and-thrust belt of the Kohat Plateau. This structural territory is comprised of various local to regional scale anticlines right from Serkia-Mitha Khattak to Kutki areas. The existing range-front anticlinal trend is well-built along the east west trending segment of the Surghar Range. These anticlinal features reveal infantile tendency from east to west and unearthing the platform rock sequences ranging from Permian to Eocene which is unconformably overlain by the Mitha Khattak Formation, equivalent facies to the Rawalpindi Group. This formation in turn has been overlain by the fluvial sediments of Siwalik Group. Overall three major anticlinal structures have been mapped from west to east as the Mitha Khattak, Makarwal and Malla Khel anticline. Different stratigraphic levels are exposed in cores of these anticlines and illustrate probable prospect that could be potential hydrocarbon reservoir horizons. The Eocene Sakesar limestone has been chosen for detailed studies. This horizon exposes along the range front which making fraction of the frontal limbs of different anticlines. Various fractures network and joints pattern has been observed in the Sakesar Limestone at different localities along the range and reveal high secondary porosity and permeability. Most of the secondary features induced and primary diagenetic opening and ruptures planes are interconnected and tenders proficient conduit lattice for munificent circulation of fluids in the Sakesar horizon. Origin of fractures and joints growth is mainly associated to force folding in response to the compressional, transpressional and trans-tensional deformation being observed in the region. The studied anticlines reveal that they are the product of fault-bend and fault-propagation folding tender excellent structural fluid trapping philosophy. The range frontal flanks reveal that different level of strata thrust over the foredeep showing variation in the subsurface level of basal detachment horizon which is too hopeful for the construction of structural traps at various levels. Blending of the structural style of the area with the sedimentary structural features of the Sakesar Limestone of Surghar Range urges that this structural province is significantly associated to make hydrocarbon reservoir potential at the stratigraphic level of Sakesar Limestone. The mapped fractured rocks assist the fluid storage aptitude and transmissivity along the medium to enhance the reservoir eminence of the Sakesar Limestone. That’s why one of the most important preconditions for the hydrocarbon accrual is in hand in the Surghar Range, Trans-Indus Ranges of the outer Himalayan Orogenic province of north Pakistan. Keywords: Surghar Range, deformation style, Sakesar Limestone, reservoir potential, tectonic, diagenetic fractures.